Bacterial communities associated with the pitcher fluids of three Nepenthes (Nepenthaceae) pitcher plant species growing in the wild. - Chou, L.; Clarke, C.; Dykes, Gary (2014)
Nepenthes pitcher plants produce modified jug-shaped leaves to attract, trap and digest insect prey. We used 16S rDNA cloning and sequencing to compare bacterial communities in pitcher fluids of each of three species, namely Nepenthes ampullaria, Nepenthes gracilis and Nepenthes mirabilis, growing in the wild. In contrast to previous greenhouse-based studies, we found that both opened and unopened pitchers harbored bacterial DNA. Pitchers of N. mirabilis had higher bacterial diversity as compared to other Nepenthes species. The composition of the bacterial communities could be different between pitcher types for N. mirabilis (ANOSIM: R = 0.340, p < 0.05). Other Nepenthes species had similar bacterial composition between pitcher types. SIMPER showed that more than 50 % of the bacterial taxa identified from the open pitchers of N. mirabilis were not found in other groups. Our study suggests that bacteria in N. mirabilis are divided into native and nonnative groups